Mammifères pleistocènes de Algoz, en Algarve: une revision - Antunes, M. Telles (2008)
At Algoz, Algarve, some mammals were found. The fauna, as revised here, corresponds to lowermost Middle Pleistocene (Biharian), just before the first glacial advance of Gunz glaciation. It is much older than it was previously regarded (Riss-Wurm interglacial). Evidence indicates an humid, swampy, riparian environment rich in plant life, and a nearby forest. Climate seems to have been rather warm (see ANTUNES et al., 1985). Age and ecology suggest that Algoz and Morgadinho, also in Algarve, are correlative (Morgadinho's age is from Villanyian to Biharian, and is thus compatible with that from Algoz). Lithology and palynological analysis corroborate this view. Algoz is the first locality of this age known in Portugal. Morgadinho and perhaps lacustrine limestones at Ponte das Lavadeiras (Faro) are more or less the same age.